IMPROVING STUDENTS’ WRITING SKILL OF DESCRIPTIVE TEXT THROUGH GUIDED QUESTION AT EIGHTH GRADE OF SMP MUSDA MEDAN IN ACADEMIC YEAR 2017/2018 - Roikestina Silaban (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2019)
The objectives of this study are to find out that through quided question can improve student’s writing skill for the eighth grade a junior high school in SMP MUSDA Medan in the academic year of 2017/2018 and to explain how to improve students’ writing skill in descriptive text through guided question at eighth grade in SMP MUSDA Medan in academic year 2017/2018. This study was conducted by using classroom action research, consists of 32 students where taken as a sample of this research. The research was conducted in two cycles. There were three meetings from each cycle in this research. The research design that used in this research were quantitative data and qualitative data. Based on the writing test score, students kept improving in every test. In the pre- test the mean score was 67,13 in post test the mean of writing score was 76,21. Based on observation sheet, it was found that teaching learning process ran well and students were actived and interested in writing descriptive text through quided question. The result of this research that by using guided question method can improve students’ writing skill in descriptive text.